Pemanfaatan Digital Marketing Sebagai Upaya Meningkatkan Perkembangan Usaha Pelaku UMKM di Desa Rajapolah Kabpaten Tasikmalaya (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy and have contributed 61% to the national GDP. Advances in digital technology have led to many changes, including in the way of marketing, especially for MSMEs which should take advantage of these advances in digital technology by entering certain online marketplaces. MSME players in Rajapolah Village, Tasikmalaya Regency are ready to take advantage of this digital technology advancement by utilizing digital marketing in marketing their products. The hope of these MSME players is that digital marketing can increase business development, so that it can restore the prestige of Rajapolah Village as a handicraft center in West Java.